Experimental Setup for Magnetoresistance Analysis of Lanthanum Manganites Thin Films - Novickij, V.; Stankevic, V.; Grainys, A.; Novickij, J.; Tolvaisiene, S.; Stankevic, T. (Elektronika ir Elektrotechnika, 2012)
A measurement and automation equipment for measuring the manganite resistance dependence on magnetic field is designed and developed in this work. Equipment consists of the electromagnet, the programmable power source, the magnetic field meter and the resistance measurement device. All devices are connected to PC by the GPIB cables and the GPIB-USB converter. The control program was created by using the LabVIEW software package. It enabled to change the steps of the current through the electromagnet in different ranges of the magnetic field and to set desired measurement accuracy and duration. The system was used for measuring of the magnetoresistance of the manganites films dependence on the magnetic field. The accuracy, which was achieved using this equipment, allows calculating anisotropy of MR of the manganites films despite to small changes of the resistance at low magnetic field. Ill. 6, bibl. 8 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.120.4.1451